Penggunaan Kartu Angka Bergambar dan Kemampuan Mengenal Lambang Bilangan Pada Anak Usia 4-5 Tahun - dinda khoirunnisa; Ari Sofia; Riswanti Rini (FKIP UNILA, 2018)
Abstract: Using Flash Card and The Ability To Recognize The Symbol Of Number Of Children Aged 4-5 Years.The problem in this study was the low ability to recognize the symbol of numbers in children aged 4-5 years. This study aimed to determine the correlation of using flash card with the ability to recognize the symbol of number of children aged 4-5 years. This type of study was quantitative study using non-exsperimental method with data analysis was man whiteny correlation. the subjects of this study were 20 children. the results showed that there was significant correlation between using flash card with the ability to recognize the symbol of numbers of children aged 4-5 years with a coefficient of Z value of -0.297 with a significance level of 5%.Keywords: cognitive, flash card, the symbol of number